The Impact of Tiktok's Online App Used on Learning Interest among High School Students - Yuliana, Lia; Hutagaol, Madeleine Intan; Hutabarat, Nova Sarah; Rahmawati, Rahmawati; Daulay, Irma Khoirot (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
TikTok Online Application is an audiovisual medium. With the increasing development, applications on mobile phones can affect learning interests among students. This research is located at SMP Negeri 6 Medan. The reason for the exploration is to figure out the Impact of Using the TikTok Online Application on Learning Interests among understudies. This research uses qualitative research methods. This research study focuses on how the impact caused by using the TikTok Online Application on Learning Interests, among learners. From the results of the study, it was found that there are 2 impacts of TikTok Online Application among students, namely positive impacts where students get new knowledge and experiences and both negative impacts, namely in often forgetting time, becoming addicted, not paying attention to health and much more. TikTok users also often use it in the wrong way or have crossed the line so that a video that smells negative and accidentally the person who saw the video has seen what he should not see.